Penicilazaphilone C, a New Azaphilone, Induces Apoptosis in Gastric Cancer by Blocking the Notch Signaling Pathway - Wang, Ming; Zhao, Huange; Hu, Juanjuan; Xu, Zhen; Lin, Yingying; Zhou, Songlin (Frontiers in Oncology, 2020)
Penicilazaphilone C (PAC) is a novel azaphilonidal derivative isolated by our group that demonstrates good anticancer activities. Considering that its molecular mechanisms remain largely unknown, here we explore the molecular mechanisms of the anticancer activities of PAC against gastric cancer.The in vitro effects of PAC on cell growth, proliferation, and apoptosis were evaluated by MTT, BrdU, MTS, colony formation assays, Hoechst 33258 staining, and flow cytometry. Related proteins were examined by western blotting. Notch receptor expression was analysed by RT-PCR. In vivo antitumor activities of PAC were observed in a nude mouse model. We found that compared to the controls, PAC treatment suppressed cell proliferation and promoted apoptosis in MGC-803 and SGC-7901 cells, and the Notch/PTEN/AKT axis was involved in the activating PAC-induced apoptosis. PAC treatment led to decreased levels of Notch (NTM), NICD, pPTEN and pAKT compared to controls. PAC-induced inhibition of Notch-related protein expression levels and the resulting apoptosis were reversed by overexpression of Notch1 (NTM) or/and Notch2 (NTM). Moreover, PAC treatment clearly inhibited tumour growth in mice both bearing tumours derived from both MGC-803 and SGC-7901 cells. This work reveals that PAC induces the apoptosis by suppressing activation of Notch receptor proteolytic cleavage and subsequently blocking the PTEN/AKT signalling axis in gastric cancer cells. Thus, PAC is a potential alternative agent for the treatment of gastric cancer.